Analysis of Weed Vegetation on Paddy Rice (Oryza sativa) Plant in Koya Village, South Tondano District - Lazar, Noviana; Naharia, Orbanus; Taulu, Marthy (Indonesian Biodiversity Journal, 2024)
Paddy Rice (Oryza sativa) is the main food commodity in Indonesia, because most of the Indonesian population's staple food is Paddy Rice. Demand for Paddy Rice continues to increase from time to time along with population growth. The aim of this research is to determine the types and control of weeds in lowland Paddy Rice plants (Oryza sativa). This research is a qualitative descriptive study using a survey method directly observing weeds in the Paddy Rice planting area in Koya village, South Tondano subdistrict. The results of research on the density, dominance, and frequency of weed types in lowland Paddy Rice plants in Koya Village, South Tondano District show that there are 4 types of weeds in lowland Paddy Rice plants in Koya Village, namely Panicum repens, Fimbristylis litotoralis, Cyperus rotundus, and Pistia stratiotes. P.repens is a grass weed, F.litoralis and C.rotundus are a weed, and P.stratiotes is a broadleaf weed. The type that has the highest relative density (KR) is P. repens, namely 3.33%, followed by F. litoratlis, namely 26.67%, and the lowest is C. rotundus and P. stratiotes, namely 20.0%. Relative Dominance Value The highest (DR) was found in the weed type P. stratiotes, namely 51.56%, then followed by C. rotundus, namely 19.27%, F. litoralis, namely 15.10%, and the lowest, P. repens, namely 14.06%. The highest relative frequency (FR) was in P. repens and C. rotundus, namely 33.33%, followed by F. litoralis, namely 22.22% and the lowest was P. stratiotes, namely 11.11%. Based on the research results, it can be concluded that there are 4 types of weeds in lowland Paddy Rice plants in Koya Village, South Tondano District with the highest weed dominance index value, namely P. stratiotes, namely 27.55787; Weed control can be done chemically, biologically, mechanically and physically.